Extrudable Compositions Containing Polymer Particles Coated with Carbon Nanotubes - Patent application
Patent Information
- Application Number
- JP2023566504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-04-28
- Publication Date
- 2025-05-01
AI Technical Summary
Current methods for preparing conductive polymer composites with high electrical conductivity require high additive loadings, which are not compatible with industrial-scale extrusion processes, limiting their applicability in mass production.
Development of core-shell particles with a thermoplastic polymer core and a carbon nanotube shell, where the CNTs are uniformly distributed, allowing for extrusion compatibility and improved electrical conductivity.
The core-shell particles enable the production of composite materials with enhanced electrical conductivity and uniform CNT distribution, suitable for industrial-scale extrusion processes, resulting in articles with improved physical and electrical properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] Cross-reference to invention This application claims the benefit of U.S. Provisional Patent Application No. 63 / 180,724, filed April 28, 2021, the contents of which are incorporated herein by reference in their entirety. FIELD OF THEINVENTION The present invention relates to the field of polymer particles comprising a carbon nanotube-based shell and their uses. [Background technology]
[0002] Various composite materials, containing conductive additives (such as carbon nanotubes, carbon fibers and metal particles) dispersed inside a polymer insulating matrix and characterized by enhanced electrical conductivity, have been the subject of both theoretical and experimental research over the last decade due to their wide variety of applications in the electrical and electronics industries. Typically, such composites are prepared by melt mixing of the conductive additives with the polymer in the molten state. To obtain materials with high electrical conductivity, high loadings of the additives are required. However, the currently available preparation methods are not compatible with the current industrial mass production processes of composites, which are mainly based on extrusion methods. Thus, there is an unmet need to develop new compositions suitable for extrusion of conductive polymer composites and thus amenable to industrial scale production. Summary of the Invention
[0003] In one aspect, a composition is provided that includes a particle comprising a polymer core in contact with a shell comprising CNTs, the polymer core comprising a thermoplastic polymer; the weight percentage of CNTs within the particle is 1-5%; and the particle size is 1-2,000 μm.
[0004] In one embodiment, the CNTs are single-walled CNTs. In one embodiment, the polymer has at least 10 13 It has a volume resistivity of Ω·cm. In another aspect, there is a composition comprising a plurality of particles of the present invention. In one embodiment, the composition further comprises fibers (eg, glass fibers). In one embodiment, the composition is characterized by a melt flow index (MFI) of 0.1-100. In one embodiment, the composition is extrudable. In another aspect, there is an article comprising the composition of the present invention. In one embodiment, the article is manufactured by a process including any of the following: extrusion, injection, hot blown film, and molding. In one embodiment, the article comprises 10 12 It is characterized by a volume resistivity of ~1 Ω·cm. In one embodiment, each of (i) the CNTs and (ii) the surfactant is present in the article at a concentration of 0.01% w / w to 5% w / w, and the article is 10 ~10 2 It is characterized by its volume resistivity in Ω·cm.
[0005] Unless otherwise specified, all technical and / or scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs.Methods and materials similar or equivalent to those described herein can be used to carry out or test embodiments of the present invention, but exemplary methods and / or materials are described below.In case of conflict, this patent specification, including definitions, will take precedence.In addition, materials, methods and examples are only illustrative and are not intended to be limiting in any way.
[0006] Further embodiments and the full scope of applicability of the present invention will become apparent from the detailed description given hereinafter. It should be understood, however, that the detailed description and specific examples, while indicating preferred embodiments of the invention, are given by way of illustration only, since various changes and modifications within the spirit and scope of the invention will become apparent to those skilled in the art from this detailed description. The present invention will now be described with reference to specific examples and embodiments so that it may be more fully understood with reference to the following illustrative drawings. [Brief description of the drawings]
[0007] [Figure 1A] 1 is a graph showing EMI attenuation of an exemplary article of the invention composed of polyamide 6 with approximately 1 wt / wt % CNTs (**) versus an article having substantially the same chemical composition and characterized by a substantially non-homogeneous distribution of CNTs (*). [Figure 1B-1C] 1B shows images of an exemplary plaque of the present invention (1B) and a control plaque (1C). As shown in FIG. 1C, CNT aggregates are visually detectable on the article surface (white arrows), indicating a non-homogeneous distribution of CNTs. [Diagram 2] FIG. 2 is a schematic diagram of the EMI attenuation measurement described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention, in some embodiments, relates to particles comprising a polymer core in contact with a shell comprising CNTs, the polymer core comprising a thermoplastic polymer; the weight percentage of CNTs in the particle is 1-10%; and the particle size is 30-2000 μm. The present invention, in some embodiments, further relates to compositions comprising a plurality of particles of the present invention, the composition being extrudable. The present invention, in some embodiments, is based on the surprising discovery that core-shell particles of the present invention comprising a polymer core having a particle size as described herein are characterized by improved physical stability (e.g., having a shell stably attached to the polymer core upon exposure thereof to a polar organic solvent, such as IPA) compared to similar particles comprising a polymer core having a particle size greater than 2 mm.
[0009] The present invention, in some embodiments thereof, relates to articles or coatings formed by extrusion of the compositions of the present invention, which articles or coatings are characterized by electrical conductivity. The present invention, in some embodiments thereof, is based on the surprising discovery that the particles of the present invention are compatible with conditions suitable for thermal processing of thermoplastic polymers (extrusion, hot mold molding, etc.), and further result in composites and / or molded articles characterized by a uniform distribution of CNTs within the polymer matrix (see Figures 1B-1C).
[0010] Before describing at least one embodiment of the invention in detail, it is to be understood that the invention is not necessarily limited in its application to the details set forth in the following description or illustrated by way of examples, as the invention is capable of other embodiments or of being practiced or carried out in various ways.
[0011] particle In one aspect, a composition is provided that includes a particle comprising a polymer core in contact with a shell comprising CNTs, the polymer core comprising a thermoplastic polymer; and a particle size of 30-2000 μm. In some embodiments, the plurality of particles of the present invention are extrudable particles that can be formed into an article by an extrusion process.
[0012] Thus, the present invention, in some embodiments thereof, relates to a composition comprising a plurality of core-shell particles, each particle comprising a meltable or extrudable core comprising a thermoplastic polymer and a shell comprising CNTs, and upon extrusion of the composition, an article is formed incorporating a predetermined weight ratio of CNTs within a polymer matrix, the polymer matrix comprising a thermoplastic polymer. Thus, the composition of the present invention can be utilized to form a homogeneous dispersion comprising a molten thermoplastic polymer and CNTs dispersed therein. In particular, the composition of the present invention can be utilized to manufacture large-scale dispersions suitable for industrial applications. In some embodiments, the article of the present invention is characterized by a uniform distribution of CNTs and further characterized by improved physical properties, such as electrical conductivity, compared to physical properties of the original polymer.
[0013] In some embodiments, the particles of the present invention are solid or in a solid state. In some embodiments, the particles of the present invention comprise a solid polymer core coated with a shell. In some embodiments, the polymer core of the particle is bonded to the shell. In some embodiments, the polymer core of the particle is stably bonded to the shell. In some embodiments, the shell of the particle is stably bonded to the polymer core.
[0014] In some embodiments, the polymer core of the particle is encapsulated by the shell. In some embodiments, at least a portion of the polymer core of the particle is encapsulated by or stably associated with the shell. In some embodiments, the polymer core of the particle is completely encapsulated by or stably associated with the shell. In some embodiments, the polymer core of the particle is surrounded by the shell. In some embodiments, the particle is substantially devoid of voids at the interface between the core and the shell.
[0015] In some embodiments, the particles of the present invention are in the form of core-shell particles (e.g., solid core-shell particles) comprising a polymer core (e.g., a solid polymer core) and a shell encapsulating the core, the core and shell being stably bonded to one another via non-covalent bonds (e.g., forming a stable particle that is substantially devoid of collapse), and the shell comprising SWCNTs. In some embodiments, the polymer core is substantially devoid of electrical conductivity. In some embodiments, the polymer core of the particles of the present invention comprises a thermoplastic polymer that is not electrically conductive.
[0016] In some embodiments, the particles of the present invention comprise or consist of a polymer core and a shell, and the polymer core and the shell have different melting temperatures. In some embodiments, the particles of the present invention comprise or consist of a polymer core and a shell, and the polymer core has a lower or higher melting temperature than the shell. In some embodiments, the core has a melting temperature of at most 650°C, at most 600°C, at most 500°C, at most 300°C, at most 200°C (including any range therebetween).
[0017] In some embodiments, the particles of the present invention comprise a shell (or coating) that is bound to the outer surface of the core. In some embodiments, the shell is stably attached to the outer surface of the core.
[0018] In some embodiments, the terms "polymer core," "solid polymer core," and "core" are used interchangeably herein.
[0019] In some embodiments, the core and / or particle of the present invention is characterized by a spherical shape. In some embodiments, the core and / or particle of the present invention is characterized by an irregular shape. The particle and / or polymer core can be generally in the form of a sphere, an imperfect sphere, a rod, a cylinder, a ribbon, a sponge, and any other shape, or a collection of these shapes, or can include a mixture of one or more shapes.
[0020] In some embodiments, at least 80%, at least 90%, at least 95%, at least 99%, at least 99.9% of the polymer core of the particle is encapsulated within or attached to the shell.
[0021] In some embodiments, the shell is in the form of a homogenous layer. In some embodiments, the chemical composition of the shell is substantially homogenous throughout any one shell dimension. In some embodiments, the shell is in the form of a layer that seals or is bonded to the core. In some embodiments, the shell is in the form of a separate layer on the core. In some embodiments, the shell and core of the particles disclosed herein are characterized by different chemical compositions and / or different dimensions (or cross-sectional areas). In some embodiments, the thickness of the shell in the composition of the present invention (e.g., a composition comprising a plurality of particles) can vary substantially. In some embodiments, the thickness of the shell is predetermined, in particular by the core size.
[0022] "Uniform" or "homogenous" is intended to refer to a size (or thickness) distribution that varies within a range including, for example, less than ±500%, ±50%, ±40%, ±30%, ±20%, or ±10%, and any value therebetween.
[0023] In some embodiments, the term "layer" refers to a substantially homogeneous material of substantially uniform thickness. In some embodiments, the shell comprises a single layer, or multiple layers. In some embodiments, the particles of the present invention comprise a single layer shell. In some embodiments, the compositions of the present invention are substantially devoid of particles disclosed herein that comprise a multi-layer shell.
[0024] In some embodiments, the CNTs comprise carbon nanostructures (e.g., a single carbon nanostructure species or multiple distinct carbon nanostructure species). The term "carbon nanostructure" is well known to those skilled in the art and specifically refers to 2D carbon materials such as carbon fibers, carbon nanotubes (single- or multi-walled, linear or branched), carbon black, graphene, and fullerenes, or any combination thereof.
[0025] In some embodiments, the CNTs are or include single-walled carbon nanotubes (SWCNTs). In some embodiments, the CNTs are conductive CNTs (e.g., conductive SWCNTs). In some embodiments, the CNTs optionally include multi-walled carbon nanotubes (MWCNTs). In some embodiments, the CNTs include SWCNTs and optionally include additional carbon nanostructures.
[0026] In some embodiments, the CNTs are characterized by an aspect ratio of 130-10,000, 130-200, 130-1,000, 1,000-5,000, 5,000-10,000, 130-7,000, 7,000-10,000, and any range therebetween.
[0027] In some embodiments, the term "bound" refers to any non-covalent bond or interaction, such as electrostatic bonds, dipole-dipole interactions, van der Waals interactions, ionotropic interactions, hydrogen bonds, hydrophobic interactions, pi-pi stacking, London forces, etc. In some embodiments, the non-covalent bond or interaction is a stable bond or interaction, where stable is as described herein.
[0028] In some embodiments, the weight percentage of shell within the particle is 0.1-10%; 0.1-1%; 1-2%; 5-10%; 1-3%; 3-5%; 5-7%; 7-10% (including any range or value therebetween).
[0029] In some embodiments, the shell thickness is 0.001-100 μm, 0.001-0.01 μm, 0.01-0.1 μm, 0.1-1 μm, 1-10 μm, 1-5 μm, 5-10 μm, 10-20 μm, 20-40 μm, 40-50 μm, 50-60 μm, 60-80 μm, 80-100 μm (including any range or value therebetween).
[0030] In some embodiments, the shell comprises carbon nanotubes (CNTs). In some embodiments, the shell comprises single-walled carbon nanotubes (SWCNTs). In some embodiments, the particles of the present invention comprise a polymer core in contact with or attached to a shell, and the shell comprises SWCNTs. In some embodiments, the CNTs (e.g., SWCNTs) are uniformly distributed on the core of the particles of the present invention.
[0031] In some embodiments, the weight percentage of SWCNTs in the particles of the present invention is 0.1-10%; 0.1-1%; 1-5%; 5-10%; 1-3%; 3-5%; 5-7%; 0.1-5%; 7-10% (including any range or value therebetween). In some embodiments, the weight percentage of SWCNTs in a particle (or composition) of the invention is between 0.00001% and 5%, between 0.00001% and 0.1%, between 0.00005% and 5%, between 0.00001% and 0.00005%, between 0.00001% and 0.0001%, between 0.00001% and 0.001%, between 0.0001% and 5%, between 0.0001% and 2%, between 0.001% and 5%, between 0.001% and 2%. %, 0.001%-1%, 0.001%-0.005%, 0.005%-0.01%, 0.01%-5%, 0.01%-2%, 0.01%-1%, 0.01%-0.5%, 0.01%-0.05%, 0.05%-0.1%, 0.1%-0.5%, 0.1%-5%, 0.5%-1%, 1%-2%, 2%-3%, 3%-5%, 5%-10% (including any ranges between these).
[0032] One skilled in the art will understand that the exact weight percentage of SWCNTs in the particles of the invention is predetermined by the desired SWCNT content of the article formed by extrusion of the composition of the invention. Thus, the final SWCNT content of the article (predetermined by the desired physical properties of the article) will predetermine the weight percentage of SWCNTs in the particles of the invention. Furthermore, the final SWCNT content of the article (predetermined by the desired physical properties of the article) can be predeterminable by the weight percentage of SWCNTs in the particles of the invention.
[0033] In some embodiments, the shell described herein comprises SWCNTs and optionally a surfactant of the present invention, and further comprises carbon nanoparticles. Non-limiting examples of carbon nanoparticles include MWCNTs, carbon black, fullerenes, nanographenes, nanographites, nanodiamonds, carbon nanorods, carbon fibers, graphene fibers, and any combination thereof. In some embodiments, the carbon nanoparticles comprise a plurality of particles, and the particles are the same. In some embodiments, the carbon nanoparticles comprise a plurality of different carbon nanoparticles.
[0034] In some embodiments, the weight percentage of CNTs in the particles of the present invention is 0.1-10%, 0.1-1%, 1-5%; 5-10%; 1-3%; 3-5%; 0.00001%-5%, 0.00001%-10%, 0.00001%-0.1%, 0.00005%-5%, 0.00001%-0.00005%, 0.00001%-0.0001%, 0.00001%-0.001%, 0.0001%-5%, 0.000 1%-2%, 0.001%-5%, 0.001%-2%, 0.001%-1%, 0.001%-0.005%, 0.005%-0.01%, 0.01%-5%, 0.01%-2%, 0.01%-1%, 0.01%-0.5%, 0.01%-0.05%, 0.05%-0.1%, 0.1%-0.5%, 0.1%-5%, 0.5%-1%, 5-7%; 7-10% (including any range or value between these).
[0035] In some embodiments, the weight percentage of CNTs within the shell of the particles of the present invention is 5-99%, 5-10%, 10-60%, 60-70%, 70-80%, 80-85%, 85-90%, 90-95%, 95-97%, 97-99% (including any range or value therebetween). In some embodiments, the SWCNT content of the shell of a particle described herein and / or of the particle is at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90% (including any range therebetween) by weight relative to the total CNT content of the particle. In some embodiments, the shell of a particle described herein and / or the multi-walled CNT (MWCNT) content of the particle is at most 30%, at most 25%, at most 20%, at most 15%, at most 10%, at most 5%, at most 1% (including any range therebetween) by weight of the total CNT content of the particle.
[0036] In some embodiments, the weight portion of CNTs within a particle of the invention, including SWCNTs and, optionally, additional carbon nanoparticles (e.g., MWCNTs, carbon black, fullerenes, graphene, etc.), is referred to herein as the CNT content of the particle.
[0037] In some embodiments, the shell is substantially devoid of polymers. In some embodiments, the shell is substantially devoid of added carbon nanoparticles. In some embodiments, the shell is substantially devoid of fibers (e.g., fiberglass, carbon fibers, etc.). In some embodiments, the shell further comprises a surfactant, hi some embodiments, the surfactant promotes binding of the CNTs (e.g., SWCNTs) to the polymer core of the particle.
[0038] In some embodiments, at least 80%, at least 85%, at least 90%, at least 93%, at least 95%, at least 97%, at least 99%, at least 99.9%, by weight of the shell of the particles of the present invention, including any range therebetween, is composed of CNTs (e.g., SWCNTs) and surfactant.
[0039] In some embodiments, the weight / weight ratio of surfactant to CNTs (e.g., SWCNTs) within a shell or particle of the invention is from 20:1 to 10:1, 10:1 to 0.1:1, 10:1 to 0.5:1, 10:1 to 8:1, 8:1 to 5:1, 5:1 to 3:1, 3:1 to 2:1, 9:1 to 7:1, 7:1 to 5:1 (including any range therebetween). In some embodiments, the surfactant weight / weight concentration within the particles of the invention is less than 0.1%, less than 0.01%. In some embodiments, the weight / weight concentration of surfactant in the particles of the invention is between 0.001% and 30%, between 0.001% and 0.1%, between 0.1% and 1%, between 1% and 10%, between 10% and 30%, between 0.00001% and 5%, between 0.00001% and 5%, between 0.00005% and 5%, between 0.00001% and 0.00005%, between 0.00001% and 0.0001%, between 0.00001% and 0.001%, between 0.0001% and 5%, between 0.0001 %~2%, 0.001%~5%, 0.001%~2%, 0.001%~1%, 0.001%~0.005%, 0.005%~0.01%, 0.01%~5%, 0.01%~2%, 0.01%~1%, 0.01%~0.5%, 0.01%~0.05%, 0.05%~0.1%, 0.1%~0.5%, 0.5%~1%, 1%~2%, 2%~3%, 3%~5%, 5%~10% (including any ranges between these).
[0040] In some embodiments, the surfactant has a binding affinity to the polymer core and to the CNTs (e.g., SWCNTs). In some embodiments, the surfactant can disperse SWCNTs in solution (organic or aqueous). In some embodiments, the surfactant can form a stable dispersion of SWCNTs in a solvent (e.g., in an organic or aqueous solution). In some embodiments, the surfactant predetermines the binding strength or stability of the core-shell particles of the present invention. In some embodiments, the surfactant predetermines the binding strength of the shell to the core in the particles of the present invention. In some embodiments, the surfactant is characterized by a solubility in organic solvents (e.g., polar solvents such as isopropyl alcohol, non-polar solvents such as toluene) and / or water of at least 1 g / L, at least 10 g / L, at least 50 g / L, at least 100 g / L (and any range therebetween).
[0041] In some embodiments, the surfactant is a cationic surfactant. In some embodiments, the surfactant comprises a polyalkylammonium. In some embodiments, the surfactant comprises a polyalkylammonium-co-polyether. In some embodiments, the surfactant is or includes an anionic surfactant (eg, SDBS, carboxymethylcellulose (CMC)) and / or a non-ionic surfactant (eg, polysiloxane). In some embodiments, the surfactant forms a layer on the core. In some embodiments, the surfactant is devoid of polyvinylpyrrolidone (PVP). In some embodiments, the surfactant is devoid of PVP and / or copolymers comprising cellulose or derivatives thereof.
[0042] In some embodiments, the surfactant lacks a surfactant suitable for carrying out dispersion polymerization (DP), also called "latex polymerization". In some embodiments, the particles of the present invention are substantially lacking surfactants adsorbed thereto (e.g., PVP, or any other suitable surfactant for DP). Dispersion polymerization refers to a polymerization method that results in the formation of small size (a few microns) polymer particles characterized by spherical shape, uniform particle size, and smooth outer surface. Furthermore, the polymer particles obtained during DP are characterized by their dispersibility in solution (e.g., aqueous solution) (they can form stable dispersions without the addition of additional surfactants and / or dispersants).
[0043] In some embodiments, the shell comprises randomly oriented or randomly distributed CNTs (e.g., SWCNTs) therein. In some embodiments, the shell comprises an entangled matrix of randomly distributed SWCNTs and surfactant molecules. In some embodiments, the surfactant molecules are attached to the CNTs (e.g., SWCNTs) and core surfaces. In some embodiments, the shell is in the form of a mat comprising a plurality of randomly oriented or randomly distributed SWCNTs in contact with a plurality of surfactant molecules.
[0044] In some embodiments, the shell comprises conductive CNTs (e.g., conductive SWCNTs). In some embodiments, the melting point of the shell is substantially predetermined by the melting point or decomposition point of the CNTs. In some embodiments, the thermal stability of the shell is predetermined by the decomposition point of the CNTs.
[0045] In some embodiments, the shell encapsulates or is stably bound to the polymer solid core. In some embodiments, the solid core of the particles of the present invention consists essentially of a polymer. In some embodiments, at least 80%, at least 85%, at least 90%, at least 93%, at least 95%, at least 97%, at least 99%, at least 99.9% by weight of the core of the particles of the present invention (including any range therebetween) is composed of a polymer. In some embodiments, the core is substantially devoid of CNTs. In some embodiments, the core is characterized by a non-uniform surface (e.g., a surface roughness of more than 1 μm, more than 5 μm, more than 10 μm, and including any range therebetween).
[0046] In some embodiments, the polymer is an organic polymer. In some embodiments, the polymer is a thermoplastic polymer. In some embodiments, the polymer in a molten state can be mixed with the shell components (e.g., SWCNTs and surfactant). In some embodiments, the polymer in a molten state can be mixed with the shell components (e.g., SWCNTs and surfactant) to produce a composite (e.g., after solidifying the mixture), the composite being as described below. In some embodiments, the polymer and SWCNTs and optionally the surfactant can form a homogenous composite.
[0047] In some embodiments, the thermoplastic polymer and / or core of the particles of the present invention have a melting point greater than 100°C, 110°C, 120°C, 150°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 500°C, 600°C, including any range or value therebetween. In some embodiments, the thermoplastic polymer and / or core of the particles of the present invention have a melting point of from 100° C. to 650° C., from 100° C. to 200° C., from 200° C. to 400° C., from 400° C. to 650° C., including any range or value therebetween.
[0048] In some embodiments, the polymer comprises a thermoplastic polymer selected from polyamides (e.g., nylons), polystyrenes, polyacrylates, polyacrylate esters, polymethacrylates, polyacrylamides, polyolefins, poly(bisphenol A-co-carbonates), poly(bisphenol A-co-terphthalates), polyvinyl alcohols, polyvinyl chlorides and polyacrylonitriles, polyphenylenes, polyetheretherketones, polyphenylene sulfides, polyetherimides, polyethersulfones, and any copolymers or combinations thereof. In some embodiments, the polymer comprises a thermoplastic resin (e.g., a short chain polymer or oligomer).
[0049] In some embodiments, the polymer comprises an acrylate-based polymer, hi some embodiments, the acrylate-based polymer is selected from the group including polyacrylate, polyacrylate ester, polymethacrylate, polyetacrylate, polymethacrylate ester, polyethacrylate, polyethacrylate ester, and any copolymer or any combination thereof.
[0050] In some embodiments, the polymer or thermoplastic polymer comprises polystyrene and / or its derivatives (eg, substituted polystyrenes such as poly(halostyrenes), poly(alkylstyrenes), etc.). In some embodiments, the polymer or thermoplastic polymer comprises a polyolefin or a mixture of polyolefins. Non-limiting examples of polyolefins include polyethylene (PE), LDPE, MDPE, HDPE, polypropylene (PP), polybutene, polyethylene-butene copolymer, polyethylene-propylene copolymer, atactic poly-α-olefin (APAO), amorphous poly-α-olefin (APAO), and syndiotactic polypropylene (SPP). Other polyolefins are known in the art. In some embodiments, the polymer or thermoplastic polymer comprises a polyamide or a mixture of polyamides, such as nylon. Various nylon polymers are known in the art, for example, nylon 6, nylon 6,6, and the like.
[0051] In some embodiments, the polymer or thermoplastic polymer that constitutes the polymer core is substantially devoid of electrical conductivity. 13 Ω cm, at least 10 14 Ω cm, at least 10 15 It is characterized by a volume resistivity in Ω·cm, and any range therebetween. In some embodiments, the polymer or thermoplastic polymer that comprises the polymer core is characterized by a surface resistivity of less than 1.05E+06, less than 1.05E+09, or less than 1.05E+12 Ω.
[0052] In some embodiments, the polymer core of the present invention is obtained by grinding or crushing a bulk polymer to obtain small polymer particles. In some embodiments, the polymer core comprises a rough outer surface (e.g., resulting from the grinding process) as described herein. Obviously, such particles are substantially non-uniformly shaped and characterized by a non-uniform particle size distribution (e.g., particles with a PDI of at least 1.5, at least 1.8, at least 2, at least 3, at least 5, at least 10, or more, and any range of PDIs therebetween). Furthermore, the particle size of the polymer core obtained by grinding or crushing a bulk polymer is usually limited to a particle size of more than 30 μm. Smaller particle sizes require the implementation of expensive and time-consuming manufacturing steps (e.g., latex polymerization) and are even less compatible with common industrial extruders due to the possibility of extruder clogging or failure. Furthermore, polymer particles with a cross section of less than 30 μm are characterized by a significantly lower feed rate, which in turn affects the final extrusion rate.
[0053] In some embodiments, the polymer core is or comprises ground particles. In some embodiments, the polymer core is or comprises ground thermoplastic polymer. In some embodiments, the core is substantially devoid of latex particles.
[0054] In some embodiments, the polymer core of the present invention further comprises a crosslinker, a plasticizer, or an additive (e.g., a colorant, a binder, a stabilizer, a radical scavenger (e.g., HALS), a UV absorber, or a combination thereof). In some embodiments, the polymer core of the present invention further comprises additives implemented in the plastics industry for the production of bulk polymers.
[0055] In some embodiments, the polymer core is substantially devoid of thermosetting polymers, hi some embodiments, the polymer core of the present invention is substantially devoid of additives, as described herein.
[0056] In some embodiments, the polymer core of the particle of the present invention is substantially devoid of surfactants bound thereto. In some embodiments, the polymer core of the particle of the present invention is substantially devoid of PVP and / or its copolymers. In some embodiments, the polymer core of the particle of the present invention is substantially devoid of PVP and / or its copolymers adsorbed on the outer surface of the polymer core. In some embodiments, the polymer core of the particle of the present invention is substantially devoid of dispersibility (ability to form a stable dispersion without additional surfactants and / or dispersants) in solution (e.g., aqueous solution). In some embodiments, the polymer core of the present invention consists essentially of at least one polymer described herein.
[0057] In some embodiments, the polymer core of the particles of the present invention is characterized by a cross-section or diameter of 30-2000 μm, 30-50 μm, 50-100 μm, 100-200 μm, 100-2,000 μm, 200-300 μm, 300-400 μm, 400-500 μm, 500-700 μm, 700-1,000 μm, 1,000-1,500 μm, 1,500-1,700 μm, 1,700-2,000 μm, and any range therebetween. In some embodiments, cross-section or diameter as used herein refers to an average value.
[0058] In some embodiments, the particles of the present invention comprise, by weight of the polymer core, 90-95%, 80-95%, 80-90%, 90-93%, 93-95%, 95-97%, 97-99% (including any range therebetween).
[0059] In some embodiments, the weight / weight ratio between the core and shell in the particles of the present invention is from 10:1 to 200:1, 10:1 to 15:1, 15:1 to 20:1, 20:1 to 25:1, 25:1 to 30:1, 30:1 to 40:1, 40:1 to 50:1, 50:1 to 70:1, 70:1 to 100:1, 100:1 to 150:1, 150:1 to 200:1, 200:1 to 1000:1 (including any range therebetween).
[0060] In some embodiments, the weight / weight ratio between polymer and SWCNTs in the particles of the present invention is from 10:1 to 100:1, from 10:1 to 15:1, from 15:1 to 20:1, from 20:1 to 25:1, from 25:1 to 30:1, from 30:1 to 40:1, from 40:1 to 50:1, from 50:1 to 100:1, from 100:1 to 1000:1 (including any range therebetween).
[0061] composition In another aspect of the invention, there is a composition comprising a plurality of particles of the invention. In some embodiments, the composition of the invention is a powder composition. In some embodiments, the composition of the invention is a solid composition. In some embodiments, the composition of the invention is in a solid state.
[0062] In some embodiments, the compositions of the present invention are substantially devoid of solvent (eg, residual solvent, such as organic solvent, aqueous solvent, or both).
[0063] In some embodiments, the composition comprises a plurality of discrete particles, hi some embodiments, the composition is substantially devoid of agglomerates of particles.
[0064] In some embodiments, the composition comprises a plurality of particles of the present invention having a particle size of 30-2,000 μm, 30-35 μm, 35-50 μm, 50-100 μm, 100-200 μm, 100-2,000 μm, 200-300 μm, 300-400 μm, 400-500 μm, 500-700 μm, 700-1,000 μm, 1,000-1,500 μm, 1,500-1,700 μm, 1,700-2,000 μm, and any range therebetween. In some embodiments, particle size as used herein refers to an average value.
[0065] As used herein, the term "average" or "mean" size refers to the diameter of the polymer particles. The term "diameter" is art-recognized and is used herein to refer to any physical diameter (also called the "dry diameter"). In some embodiments, the dry diameter of particles prepared according to some embodiments of the present invention may be assessed using transmission electron microscope (TEM), particle size analyzer, or scanning electron microscope (SEM) imaging.
[0066] In some embodiments, the composition is substantially devoid of particles having a polymer core with a cross-section or diameter less than 50 μm, less than 40 μm, less than 35 μm, less than 33 μm, less than 31 μm, less than 30 μm, less than 25 μm, less than 20 μm, and any range therebetween.
[0067] In some embodiments, the size of at least 90% of the particles varies within a range of greater than ±100%, ±50%, ±200%, ±300%, ±400%, ±500% (including any value therebetween).
[0068] In some embodiments, the plurality of particles has a substantially non-uniform size. In some embodiments, the plurality of particles has a substantially non-uniform shape. In some embodiments, the plurality of particles is polydisperse (e.g., characterized by a polydisperse size distribution). The particles may typically be shaped into spheres, imperfect spheres (particularly of a size that allows attachment to a substrate), rods, cylinders, ribbons, sponges, and any other shape, or may be in the form of a collection of these shapes, or may include a mixture of one or more shapes.
[0069] In some embodiments, the plurality of particles has a polymer core characterized by a substantially non-uniform shape and / or cross-section, hi some embodiments, the plurality of particles comprises a polydisperse polymer core. In some embodiments, the standard deviation of the average cross section of the polymer core is at least 50%, at least 100%, at least 200%, at least 500% (including any value therebetween).
[0070] In some embodiments, the composition of the present invention further comprises additional particles, such as polymer particles. In some embodiments, the additional particles comprise thermoplastic polymer particles. In some embodiments, the additional particles comprise a thermoplastic polymer, the thermoplastic polymer being as described herein. In some embodiments, the thermoplastic polymer of the additional particles is a different polymer than the polymer of the polymer core of the particle of the present invention, or is the same polymer. In some embodiments, the composition of the present invention further comprises an additive. In some embodiments, the additive is a non-conductive material. In some embodiments, the additive is or comprises a polymeric material (e.g., a thermoplastic polymer such as those described herein), a glass material, a ceramic material, or any combination thereof. In some embodiments, the additive is compatible with any one of the heat treatment techniques disclosed herein, such as extrusion, hot mold molding, etc. (e.g., it does not decompose or agglomerate during heat treatment, and / or is compatible with the thermoplastic polymer so that there is no detectable phase separation upon melting of the polymer core).
[0071] In some embodiments, the additive is a solid. In some embodiments, the additive is in the form of a particulate material (e.g., fibers, particles, meshes, etc.). In some embodiments, the additive is or comprises a polymer particle. In some embodiments, the polymer particle comprises or consists essentially of a thermoplastic polymer. In some embodiments, the polymer particle comprises the same polymer (e.g., having substantially the same chemical composition and / or the same physical properties, e.g., melting point, glass transition point, molecular weight, etc.) as the core of the particle of the present invention. In some embodiments, the additive (e.g., in the form of a polymer particle) comprises a polymer that is compatible with the polymer that constitutes the core of the particle of the present invention. The term "compatibility" is well known in the art and refers in particular to the miscibility of compounds (e.g., polymers in the molten state).
[0072] In some embodiments, the compositions of the present invention comprise from 1-99.9%, 5-99.9%, 5-90%, 10-99.9%, 50-99.9%, 60-99.9%, 70-99.9% (and any range therebetween) of an additive by weight of the composition, wherein the additive is as described herein.
[0073] In some embodiments, the composition of the present invention further comprises fibers. In some embodiments, the composition of the present invention further comprises glass fibers. In some embodiments, the composition of the present invention further comprises polymer particles as described herein.
[0074] In some embodiments, the weight / weight concentration of the particles of the present invention in a composition (e.g., an extrudable composition) is 1-100%, 1-10%, 10-20%, 20-30%, 30-50%, 50-70%, 70-80%, 80-100% (including any range therebetween).
[0075] In some embodiments, the weight / weight concentration of the particles of the present invention in the composition predetermines the flowability of the composition. In some embodiments, the melt flow index (MFI) of the composition of the present invention is predeterminable by the weight / weight concentration and / or chemical structure of the surfactant in the particles of the present invention.
[0076] In some embodiments, the compositions of the present invention are compatible with extrusion machines. In some embodiments, the compositions of the present invention are extrudable. In some embodiments, the compositions of the present invention can be processed via an extrusion process. In some embodiments, the compositions of the present invention are configured for extrusion. In some embodiments, the physical properties of the compositions of the present invention (e.g., particle size, chemical composition, ratio between CNTs and thermoplastic polymer) are compatible or suitable for an extrusion process.
[0077] In some embodiments, the extrudable composition is characterized by an MFI of from 0.1 to 100, from 0.1 to 1, from 1 to 10, from 10 to 50, from 50 to 100, including any range therebetween.
[0078] In some embodiments, the compositions of the present invention are characterized by a feed rate ranging from 1 to 7,000 kg / hr, 1 to 10 kg / hr, 10 to 100 kg / hr, 100 to 1,000 kg / hr, 1,000 to 7,000 kg / hr, including any range therebetween.
[0079] In some embodiments, the particles of the present invention are chemically and / or physically stable. In some embodiments, a stable composition (e.g., a composition of the present invention) is substantially devoid of aggregates. In some embodiments, an aggregate comprises a plurality of particles that are adhered or bonded to each other.
[0080] In some embodiments, a particle of the present invention is said to be stable if the particle substantially maintains its structure, and its physical properties, and / or the shell of the particle remains in contact with or attached to the core of the particle (e.g., substantially lacks disintegration).
[0081] In some embodiments, particles of the invention are referred to as chemically stable when the particles substantially maintain their chemical composition.
[0082] In some embodiments, the particles of the present invention are substantially chemically and / or physically stable (e.g., the particles substantially maintain their structural and / or functional properties, such as extrudability, stability, absence of degradation, etc.) for periods including at least 1 month, at least 2 months, at least 6 months, at least 12 months, at least 2 years, at least 3 years, at least 10 years, and any ranges therebetween, substantially as described hereinbelow. In some embodiments, the particles of the present invention are substantially stable for periods described herein at storage conditions including temperatures below the melting point of the thermoplastic polymer.
[0083] Goods In another aspect of the invention, there is an article made by extrusion of the composition of the invention. In some embodiments, the article is an extrudate of the composition of the invention. In some embodiments, the article is made by processing the composition of the invention. In some embodiments, the processing is by a process selected from extrusion, injection, hot blown film, molding (e.g., casting, compression molding, rotational molding) or any combination thereof. In some embodiments, the composition of the invention is moldable or processable to obtain the article of the invention.
[0084] In some embodiments, the article comprises a wall, the wall being processed from the composition of the present invention. In some embodiments, the wall consists essentially of a polymer matrix and a plurality of CNTs embedded or incorporated therein. In some embodiments, the plurality of CNTs are homogeneously distributed within the wall and / or within the polymer matrix.
[0085] In some embodiments, each of the plurality of CNTs is contacted or bound with one or more surfactant molecules. In some embodiments, the surfactant molecules substantially prevent CNT assembly. In some embodiments, the surfactant enhances the compatibility of the CNTs and the polymer matrix. In some embodiments, the surfactant enhances the stability of the composition. In some embodiments, the surfactant enhances or induces the dispersibility of the CNTs within the polymer matrix. In some embodiments, the surfactant prevents the separation of the CNTs and the thermoplastic polymer.
[0086] In some embodiments, the polymer matrix comprises a thermoplastic polymer, as described below. In some embodiments, the polymer matrix is an entangled matrix of randomly distributed polymer chains and surfactant molecules. In some embodiments, the polymer chains are in contact with the surfactant molecules, thereby forming a matrix. In some embodiments, the polymer chains are randomly distributed within the matrix. In some embodiments, the matrix is substantially devoid of aligned or oriented polymer chains. In some embodiments, the matrix is substantially devoid of aligned or oriented polymer chains in a particular direction.
[0087] In some embodiments, the wall is characterized by a thickness including 100 nm to 10 cm, 100 nm to 1 μm, 1 μm to 10 cm, 10 μm to 10 cm, 10 μm to 5 cm, 20 μm to 10 cm, 30 μm to 10 cm, 40 μm to 10 cm, 50 μm to 10 cm, 100 μm to 10 cm, 10 μm to 1 cm, 1 to 10 cm, 1 to 5 cm, 5 to 10 cm, 50 μm to 5 cm, 50 μm to 1 cm, 50 μm to 3 cm, and any range therebetween.
[0088] In some embodiments, the walls and / or articles are characterized by length / width dimensions ranging from 0.1 cm to 100 m, 1 cm to 100 m, 1 cm to 1 m, 1 to 100 m, 1 to 10 m, 10 m to 100 m, including any range therebetween.
[0089] In some embodiments, the term wall refers to a structural element of the article, and the shape of the wall substantially predetermines the shape of the article. In some embodiments, the wall is characterized by a uniform thickness. In some embodiments, the wall is characterized by a non-uniform thickness. In some embodiments, the wall has a 2D or 3D shape. In some embodiments, the wall is either a sphere, a hemisphere, a hollow sphere, a cylinder, a hollow cylinder, a hollow hemisphere, a cone, a pyramid, a horseshoe, or any other 3D shape. In some embodiments, the wall is substantially continuous. In some embodiments, the wall includes one or more openings or cuts. In some embodiments, the openings are distributed in the form of a pattern on or in the wall. In some embodiments, the wall is a perforated wall. In some embodiments, the openings or perforations are distributed in the form of a pattern on or in the wall. In some embodiments, the wall is in the form of a net.
[0090] In some embodiments, the article is produced by a process comprising: a) providing a composition of the invention under conditions suitable for extrusion, thereby obtaining an extrudate; and b) shaping the extrudate to obtain an article of the invention. In some embodiments, step b) is performed after performing step a). In some embodiments, step a) further comprises drying the extrudates under suitable conditions, for example by exposing them to a temperature between 30 and 200° C. (or at least 5° C., at least 10° C., or at least 20° C. below the melting point of the thermoplastic polymer that constitutes the particles of the invention). In some embodiments, step b) is performed to obtain an article characterized by a predetermined shape.
[0091] In some embodiments, step b) is carried out by a process selected from extrusion, injection, hot blown film, molding (eg, casting, compression molding, rotational molding), or any combination thereof. In some embodiments, the extrudates are in the form of plates, films, particulate matter (e.g., granules), or are characterized by a three-dimensional shape, or are characterized by at least one dimension between 1 mm and 100 mm, and any range therebetween, In some embodiments, the extrudates lack any distinct three-dimensional shape. In some embodiments, the extrudate is moldable by a process selected from extrusion, injection, hot blown film, molding (e.g., casting, compression molding, rotational molding), or any combination thereof. In some embodiments, the term "moldable" or "processable" refers to the ability of a composition to obtain a predetermined shape.
[0092] In some embodiments, the article is a composite material. In some embodiments, the article of the present invention is a solid composite. In some embodiments, the article of the present invention is in the form of a layered composite. In some embodiments, the entire article or composite material (also used herein as "composite") of the present invention is substantially homogeneous. In some embodiments, the CNTs are uniformly distributed within the entire article of the present invention. In some embodiments, the CNTs are uniformly distributed within the polymer matrix of the present invention.
[0093] As used herein, a "composite material" is a material that is produced from two or more component materials that, when mixed, result in a material with different properties than the individual elements, especially those that have dissimilar chemical or physical properties.
[0094] In some embodiments, a composite refers to a substantially homogenous material that cannot be easily separated into individual components (e.g., the CNTs of the present invention, the surfactant, and the thermoplastic polymer). In some embodiments, the composite is substantially devoid of phase separation or collapse (also referred to herein as a "stable" composite). In some embodiments, the composite is substantially devoid of a multi-layer structure. As one skilled in the art will appreciate, there are three types of composites (e.g., nanocomposites): non-intercalated (microcomposites), intercalated, or exfoliated nanocomposites.
[0095] In some embodiments, a homogeneous composite as used herein comprises CNTs substantially uniformly distributed within a matrix. In some embodiments, a homogeneous composite as used herein comprises CNTs substantially uniformly embedded within a matrix. In some embodiments, a homogeneous composite as used herein is substantially devoid of CNT aggregates (or agglomerates). In some embodiments, a homogeneous composite as used herein comprises aggregates of 20% or less, 15% or less, 10% or less, 5% or less, 3% or less, 1% or less, and any range therebetween, by weight percent relative to the total CNT content of the composite of the present invention.
[0096] In some embodiments, a homogenous composite, as used herein, contains no more than 20%, no more than 15%, no more than 10%, no more than 5%, no more than 3%, no more than 1% (including any range therebetween) of aggregates relative to the total CNT content within the cross-section of the composite. One of ordinary skill in the art will appreciate that the degree of CNT aggregation can be assessed by analyzing the microstructure of the material, including but not limited to TEM or SEM photographs. In some embodiments, at least 70%, at least 80%, at least 90%, at least 92%, at least 95%, at least 97%, at least 99% of the CNTs of the composite are organized into a plurality of distinct regions (or distinct populations), each region characterized by a width (or cross-sectional) and / or length dimension of 1-500 nm, 1-100 nm, 1-200 nm, 1-10 nm, 1-50 nm, 10-500 nm, 10-100 nm, 50-500 nm, 50-100 nm, 100-500 nm, 50-200 nm, or less than 10 μm, less than 5 μm, less than 1 μm, including any range therebetween.
[0097] In some embodiments, the CNT aggregates are characterized by at least one dimension (e.g., thickness) of at least 1 μm, at least 5 μm, at least 10 μm, at least 50 μm, at least 100 μm, at least 500 μm (including any range therebetween). In some embodiments, the at least one dimension of the aggregates refers to an average value.
[0098] In some embodiments, the article is capable of and / or configured for attenuation of electromagnetic radiation or electromagnetic interference (EMI), hi some embodiments, the wall and / or the article are shaped to provide EMI attenuation (e.g., EMI reflection, EMI dissipation, or both).
[0099] The homogeneity (e.g., the presence of CNT aggregates) of the composite material of the present invention can be assessed by using appropriate microscopic analysis of the material surface, such as by TEM, SEM, etc. Analysis of the micrographs (e.g., TEM and / or SEM photographs) can be performed, for example, by image processing software, as is well known in the art. Additionally, homogeneity can be assessed by examining the composition of the article (e.g., measuring the concentration of CNTs and / or surfactants) at at least three different locations. The standard deviation of the measured concentration values is assumed to be 20% or less, 10% or less, 5% or less, 1% or less (including any range therebetween). Alternatively, homogeneity can be assessed by testing the EMI (electromagnetic interference) attenuation or shielding properties of the composition or article, as shown in the Examples section.
[0100] In some embodiments, the articles of the present invention are formed by providing an extrudate under conditions suitable for extrusion, injection, hot blown film, molding (e.g., casting, compression molding, rotational molding), or any combination thereof.
[0101] In some embodiments, the article is solid. In some embodiments, the article comprises a polymer matrix and a plurality of CNTs (e.g., SWCNTs) embedded or incorporated therein. In some embodiments, the plurality of CNTs (e.g., SWCNTs) are homogeneously distributed within the matrix. In some embodiments, the polymer matrix comprises a thermoplastic polymer, as described herein. In some embodiments, the polymer matrix is an entangled matrix of randomly distributed polymer chains and surfactant molecules. In some embodiments, the polymer chains are in contact with the surfactant molecules, thereby forming a matrix. In some embodiments, the polymer chains are randomly distributed within the matrix. In some embodiments, the matrix is substantially devoid of aligned or oriented polymer chains. In some embodiments, the matrix is substantially devoid of aligned or oriented polymer chains in a particular direction.
[0102] In some embodiments, the thermoplastic polymer of the present invention forms a matrix and the CNTs (e.g., SWCNTs) are contacted with or bound to it. In some embodiments, the CNTs (e.g., SWCNTs) are physisorbed and / or chemisorbed on or within the matrix. In some embodiments, the binding is via non-covalent bonds. In some embodiments, the CNTs (e.g., SWCNTs) are encapsulated by the matrix. In some embodiments, the CNTs (e.g., SWCNTs) provide reinforcement to the composite. In some embodiments, the CNTs (e.g., SWCNTs) induce or enhance electrical conductivity of the composite (or article of the present invention).
[0103] In some embodiments, the article is a composite material. In some embodiments, the article of the present invention is a solid composite. In some embodiments, the article of the present invention is in the form of a layered composite. In some embodiments, the entire article or composite material of the present invention (also used herein as "composite") is substantially homogenous.
[0104] As used herein, a "composite material" is a material formed from two or more component materials that, when mixed, result in a material having different properties than the individual elements, especially materials that have dissimilar chemical or physical properties.
[0105] In some embodiments, a homogeneous composite refers to a material that cannot be easily separated into its individual components (e.g., the CNTs of the present invention, the surfactant, and the thermoplastic polymer).As one of ordinary skill in the art will appreciate, there are three types of nanocomposites: non-intercalated (microcomposites), intercalated, or exfoliated nanocomposites.
[0106] The properties of nanocomposites strongly depend on the CNT concentration, surface activity and their distribution in the polymer matrix. The main challenge in the development of nanocomposites or articles characterized by high electrical conductivity is the uniform distribution of CNTs in the polymer medium. One of the possible solutions described herein is the production of core-shell particles described herein, which results in better homogeneity than current industrial methods.
[0107] In some embodiments, the article or composition of the present invention consists essentially of a thermoplastic polymer, CNTs, and a surfactant, as described herein. In some embodiments, the weight percent of the article of the present invention is at least 50%, at least 60%, at least 70%, at least 80%, at least 85%, at least 90%, at least 93%, at least 95%, at least 97%, at least 99%, and any range therebetween, is composed of a thermoplastic polymer. In some embodiments, at least 80%, at least 90%, at least 95%, at least 99%, or at least 99.9% of the polymer matrix is composed of a thermoplastic polymer.
[0108] In some embodiments, the CNTs and / or surfactant (and optionally any additional components of the composition) are miscible or compatible with the thermoplastic polymer in the molten state. In some embodiments, the thermoplastic polymer in the molten state is miscible or compatible with the additional components of the composition so as to form a composite (e.g., upon cooling at a temperature below the glass transition of the thermoplastic polymer). In some embodiments, the thermoplastic polymer in the molten state is compatible with the CNTs, such that the resulting mixture is substantially devoid of phase separation and / or aggregation.
[0109] In some embodiments, the polymer in the molten state can be mixed with additional components of the composition (e.g., after solidification of the mixture) to produce a homogeneous composite. In some embodiments, the thermoplastic polymer and the CNTs, and optionally, a surfactant, can form a homogeneous composite.
[0110] In some embodiments, an article of the invention comprises CNTs (e.g., SWCNTs) and a surfactant embedded in a polymer matrix, and the weight / weight concentration of the surfactant and / or CNTs in the article is 0.01%-5%, 0.01%-0.05%, 0.05%-0.1%, 0.1%-0.5%, 0.5%-1%, 1%-2%, 2%-3%, 3%-5%, 5%-10% (including any range therebetween).
[0111] In some embodiments, an article of the invention includes CNTs (e.g., SWCNTs) and a surfactant embedded in a polymer matrix, and the weight / weight concentration of the surfactant and / or CNTs in the article is between 0.00001% and 5%, between 0.00001% and 0.01%, between 0.00005% and 5%, between 0.00001% and 0.00005%, between 0.00001% and 0.0001%, between 0.00001% and 0.001%, between 0.0001% and 5%. %, 0.0001%-2%, 0.001%-5%, 0.001%-2%, 0.001%-1%, 0.001%-0.005%, 0.005%-0.01%, 0.01%-5%, 0.01%-2%, 0.01%-1%, 0.01%-0.5%, 0.01%-0.05%, 0.05%-0.1%, 0.1%-0.5%, 0.5%-1%, 1%-2%, 2%-3%, 3%-5%, 5%-10% (including any ranges between these).
[0112] In some embodiments, the content of non-SWCNT carbon nanostructures (e.g., MWCNTs, etc.) in the articles and / or compositions described herein is up to 30%, up to 25%, up to 20%, up to 15%, up to 10%, up to 5%, up to 1% by weight of the total CNT content of the article (including any range therebetween).
[0113] In some embodiments, total CNT content is referred to herein as the weight part of SWCNTs and optionally at least one additional carbon nanostructure (e.g., MWCNTs, carbon black, fullerenes, graphene, etc.) within an article of the present invention.
[0114] In some embodiments, the composition is substantially devoid of added carbon nanoparticles. In some embodiments, the composition is substantially devoid of inorganic materials (e.g., metals, glasses, minerals, any particles thereof, or any fibers). In some embodiments, the composition is substantially devoid of fibers (e.g., carbon fibers, etc.). In some embodiments, the terms carbon nanostructures and carbon nanoparticles are used interchangeably herein.
[0115] In some embodiments, the electrical conductivity of the article (or composite) is at least 50%, at least 100%, at least 200%, at least 500%, at least 1,000%, at least 10,000%, at least 1,000,000,000%, and any range therebetween, greater than the electrical conductivity of the original polymer (e.g., without the CNTs and / or surfactants).
[0116] In some embodiments, the electrical conductivity of the article is at least 10, at least 100, at least 1,000, at least 10,000, at least 100,000, at least 1,000,000, at least 10,000,000 times greater than the electrical conductivity of the original polymer, including any range therebetween.
[0117] In some embodiments, the article of the present invention comprises 10 12 ~1Ω cm, 10 12 ~10 10 Ω cm, 10 10 ~10 8 Ω cm, 10 8 ~10 6 Ω cm, 10 6 ~10 4 Ω cm, 10 4 ~10 2 Ω cm, 10 2 It is characterized by a volume resistivity of ~1 Ω·cm, including any range therebetween.
[0118] In some embodiments, the articles of the present invention are physically stable. In some embodiments, the stable articles are substantially devoid of phase separation (e.g., collapse of the composite with separation between the CNTs and the polymer matrix). In some embodiments, the stable articles are substantially devoid of cracks, deformations or other physical defects. In some embodiments, the stable articles substantially retain their shape, dimensions and / or physical properties such as mechanical strength, electrical conductivity, etc.
[0119] In another aspect of the invention, a coated substrate is provided that comprises a substrate in contact with an article of the invention in the form of a coating.
[0120] In some embodiments, the coating comprises a composite (e.g., a solid composite) disclosed herein. In some embodiments, the coating is in the form of a film. In some embodiments, the film forms a substantially uniform layer. In some embodiments, the coating is in the form of a solid. In some embodiments, the coating is substantially devoid of solvent (e.g., any residual solvent from the manufacturing process). In some embodiments, the weight / weight concentration of residual solvent in the coating is less than 5%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.1% (including any ranges therebetween).
[0121] In some embodiments, the coating layer described in any of the respective embodiments is incorporated in or on at least a portion of a substrate. In some embodiments, the coating layer described in any of the respective embodiments is incorporated in and / or on at least a portion of at least one surface of a substrate. In some embodiments, the terms "coating layer" and "coating" are used interchangeably herein.
[0122] Without being bound to a particular theory or mechanism, it is hypothesized that the polymer provides adhesive properties to the substrate, and the CNTs (e.g., SWCNTs) provide additional physical properties (e.g., electrical conductivity, mechanical strength, etc.) to the final coating.
[0123] In some embodiments, the coating layer is referred to as a "layer," e.g., represents 100% surface coverage. In some embodiments, the coating layer is about 90%, about 80%, about 70%, about 60%, about 50%, about 40% surface coverage (including any value therebetween). In some embodiments, the substrate further comprises multiple coating layers.
[0124] In some embodiments, the coating layer is homogeneously deposited on the surface, hi some embodiments, the coating is substantially devoid of cracks, scratches, and / or other structural defects.
[0125] In some embodiments, the coating is bonded or adhered to the substrate. In some embodiments, the coating is embedded on or within the substrate. In some embodiments, the coating is physisorbed to the substrate. In some embodiments, the coating is stably attached to the substrate.
[0126] In some embodiments, the coating is in contact with at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 70%, at least 90%, at least 95%, at least 99%, at least 99.9% of the substrate surface. In some embodiments of the present invention, a substrate is provided incorporating in and / or on at least a portion thereof a disclosed coating layer as described herein.
[0127] In some embodiments, the article is substantially stable (e.g., the article substantially maintains its structural and / or functional properties, such as physical stability and / or the absence of disintegration or erosion of a coating layer), substantially as described below, for a period including at least 1 month, at least 2 months, at least 6 months, at least 12 months, at least 2 years, at least 3 years, at least 10 years, and any range therebetween.
[0128] In some embodiments, the article is substantially stable upon exposure to thermal radiation. In some embodiments, the thermal radiation includes temperatures of 30-100° C., −50-0° C., 0-10° C., 10-30° C., 30-50° C., 50-70° C., 70-100° C., 100-150° C., and any range therebetween. In some embodiments, the thermal radiation includes temperatures below the melting point of the thermoplastic polymer.
[0129] As used herein, the term "stable" refers to the ability of an article to substantially maintain its structural, physical, and / or chemical properties. In some embodiments, an article is said to be stable if it substantially maintains its structure (e.g., shape and / or dimensions such as thickness, length, etc.), substantially as described below.
[0130] In some embodiments, a coating layer is referred to as stable if it is substantially devoid of cracks, deformations, or any other surface irregularities.
[0131] In some embodiments, the terms "coating" and "coating layer" are used interchangeably herein.
[0132] Substrates that can be used according to some embodiments of the present invention may have organic or inorganic surfaces, including, but not limited to, glass surfaces; porcelain surfaces; ceramic surfaces; silicon or organosilicon surfaces; metal surfaces (e.g., stainless steel); polymeric surfaces, such as plastic surfaces, rubbery surfaces, paper; wood; woven, knitted, or uncovered fabrics; mineral (rock or glass) surfaces, wool, silk, cotton, linen, leather, plastic surfaces, and surfaces that include or are made of inorganic polymers, such as polymers, nylon, silicon rubber, or glass, or may include or be made of any of the aforementioned materials. Substrates are selected from, but not limited to, polycarbonate, polyester, nylon, and metal foils, such as aluminum foil. In some embodiments, the substrate is in the form of a continuous layer or a woven or non-woven substrate.
[0133] general As used herein, the term "about" refers to ±10%. The terms "comprises, comprising, includes, including," "having," and their cognates mean "including but not limited to." The term "consisting of" means "including and limited to." The term "consisting essentially of" means that a composition, method, or structure may include additional ingredients, steps, and / or moieties only if the additional ingredients, steps, and / or moieties do not materially alter the basic and novel characteristics of the claimed composition, method, or structure. The word "exemplary" is used herein to mean "serving as an example, instance, or illustration." Any embodiment described as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments and / or to exclude the incorporation of features from other embodiments. The phrase "optionally" is used herein to mean "provided in some embodiments and not provided in other embodiments." Any particular embodiment of the invention may include multiple "optional" features unless such features are inconsistent. The term "enhance" refers to a difference of at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 80%, at least 100%, at least 150%, at least 200%, at least 250%, at least 300% (including any range or value therebetween). As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. For example, the term "a compound" or "at least one compound" may include a plurality of compounds, including mixtures thereof.
[0134] Throughout this application, various embodiments of the present invention may be presented in a range format. It should be understood that the description in range format is merely for convenience and brevity and should not be construed as an inflexible limitation on the scope of the present invention. Thus, the description of a range should be considered to have all possible subranges specifically disclosed, as well as individual numerical values within that range. For example, the description of a range such as 1-6 should be considered to have specifically disclosed subranges (e.g., 1-3, 1-4, 1-5, 2-4, 2-6, 3-6, etc.), as well as individual numerical values within that range (e.g., 1, 2, 3, 4, 5, and 6). This is true regardless of the breadth of the range.
[0135] Whenever a numerical range is given herein, it is intended to include any recited numbers (fractional or integer) within the given range. The phrases "ranging between" a first given number and a second given number, and "ranging from" a first given number to a second given number, are used interchangeably herein and are intended to include the first and second given numbers and all fractions and integers therebetween.
[0136] As used herein, the term "substantially" refers to a percentage including at least 60%, at least 70%, at least 80%, at least 85%, at least 90%, at least 95%, at least 97%, at least 99%, at least 99.9%, and any range or value therebetween. In some embodiments, the terms "substantially" and "consisting essentially of" are used interchangeably herein.
[0137] The term "method" as used herein refers to manner, means, techniques, and procedures for accomplishing a given task, and includes, but is not limited to, such manner, means, techniques, and procedures known to a practitioner in the arts of chemistry, pharmacology, biology, biochemistry, and medicine or readily developed by a practitioner in the arts of chemistry, pharmacology, biology, biochemistry, and medicine from known manner, means, techniques, and procedures.
[0138] As used herein, the term "treatment" includes inhibiting, substantially suppressing, slowing, or reversing the progression of a condition, substantially improving the clinical or cosmetic symptoms of a condition, or preventing the appearance of clinical or cosmetic symptoms of a condition.
[0139] It will be understood that certain features of the invention that are, for clarity, described in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention that are, for brevity, described in the context of a single embodiment, may also be provided separately or in any suitable subcombination or as otherwise suitable in other described embodiments of the invention. Certain features described in the context of various embodiments should not be regarded as essential features of those embodiments, unless the embodiment is inoperable without those elements.
[0140] Various embodiments and aspects of the present invention as described above and claimed below are found experimentally supported in the following examples. Reference is now made to the following examples, which together with the above descriptions, illustrate certain embodiments of the present invention in a non-limiting manner.
[0141] Working Example Example 1 Preparation of nylon 6-based core-shell particles Polymer particles: Polyamide (PA) nylon 6 powder, particle size 30-1300 μm (purchased from LANXESS, DOMO, BASF, etc.). SWCNT: average outer diameter 1.6 nm, length >5 μm. Surfactant: Polyether copolymer based surfactant.
[0142] Nylon 6 powder was coated to obtain exemplary core-shell particles of the present invention, with a core to shell weight / weight ratio of about 100:1. The core-shell particles of the invention (in the form of a dry powder) were extruded by a twin screw extruder, Coperion, ZSK 18 MegaLab, D=18 mm, 48 L / D. The following compositions were demonstrated and tested: [Table 1] [Table 2]
[0143] Polycarbonate and polyethylene powders have been successfully incorporated into the above coating process to yield conductive articles. Additional surfactants, such as polyester-based block copolymers, and polyacrylic-co-maleic acid, have been successfully incorporated for the production of the core-shell polymer particles of the present invention. Exemplary conductive articles were then formed by extrusion of the core-shell particles. The articles tested showed enhanced conductivity (10 12 ~10 6 The volume resistivity of the specimen was 100 μm. Additionally, coating was also performed in aqueous SWCNT dispersions with SDBS, CMC as surfactants. Exemplary conductive articles were then formed by extrusion of the core-shell particles. The articles tested showed enhanced conductivity (10 12 ~10 6 The volume resistivity of the specimen was 100 μm.
[0144] Example 2 Coating of nylon 6-based millimeter-sized core-shell particles Polymer particles: Polyamide (PA) nylon 6 pellets, particle size = about 2-3 mm (purchased from LANXESS, DOMO, BASF, etc.). SWCNT: average outer diameter 1.6nm, length>5μm Surfactant: Polyether copolymer-based surfactant
[0145] Coating was carried out according to the conditions described in Example 1. The shell adhesion was then tested by extracting the resulting particles with IPA. Surprisingly, the inventors observed that the resulting particles were unstable (i.e., the particles were subject to disintegration upon contact with polar solvents) and that the shell was easily separated from the polymer core by solvent extraction with IPA. Thus, upon incorporation of polymer particles with a particle size of more than 2 mm, the resulting core-shell particles were easily subject to disintegration. Apparently, the resulting particles were not extrudable because the SWCNT-based shell was disintegrated during the feeding stage.
[0146] Example 3 Exemplary articles of the invention comprising walls made of the compositions of the invention were produced by extrusion and / or molding of core-shell particles as described herein and containing small amounts of CNTs (see Table 1).
[0147] Polyamide (polyamide 6) and SWCNT-based core-shell particles were incorporated for the manufacture of exemplary articles in the form of plate specimens. The composition of the core-shell particles was as follows: polyamide (PA6) powder, particle size 30-1300μ, (purchased from LANXESS, DOMO, BASF, etc.); SWCNT: 1 wt% (average outer diameter 1.6 nm, length >5 μm, purchased from OCSiAl); Surfactant: polyether copolymer-based surfactant.
[0148] Core-shell particles were prepared as follows: Nylon 6 particles were coated with SWCNTs to obtain Nylon 6 / CNT core-shell particles. The weight / weight ratio of core to shell is about 100:1 to 10:1. The chemical composition of the exemplary core-shell particles is identical to the composition of the articles shown in Table 1 below.
[0149] In an exemplary embodiment, the articles of the present invention were produced by extrusion of the exemplary core-shell particles in a twin screw extruder (Coperion, ZSK 18 MegaLab, D=18 mm, 48 L / D) under suitable conditions.
[0150] The extrudate was then dried at about 40-100° C. for about 0.5-10 hours. The dried extrudate was further molded (e.g., by compression molding) to obtain a 10 cm*10 cm plate specimen (approximately 300 μm thick). The EMI attenuation of the exemplary articles processed from the core-shell particles described herein was tested as described below and compared to (i) the original polymer lacking CNTs, and (ii) a control article (designated P9-158-1) having the same composition processed from the core-shell particles of the present invention. Figure 1C is a micrograph showing the non-homogenous distribution of CNTs within the polymer matrix of the control article.
[0151] P9-158-1 was prepared by molding (eg, compression molding) a mixture of polyamide 6 and 0.2 wt % CNTs to obtain a non-homogeneous 10 cm*10 cm plate specimen (approximately 300 μm thick).
[0152] The measurements were carried out in a laboratory at the Schlesinger Center for Radiation Sources and Applications at Ariel University, Israel. Briefly, the transmit and receive antennas connected to a network analyzer are aligned with each other (as shown in Figure 2). A calibration measurement S21 is performed without a test plate (free field). For the measurement, the test plate is introduced into the centre of the radiated electromagnetic field perpendicular to the antennas, so that the centre of the test plate is located on an imaginary line between the transmitting and receiving antennas. The sample is aligned perpendicular to the direction of the electromagnetic wave at the height of the electromagnetic wave of transmission. The transmission characteristics are obtained by measuring the S21 parameter with a network analyzer.
[0153] The results of this experiment are shown in Figure 1A. The values in Figure 1A are referred to as the EMI attenuation relative to the attenuation of the parent polymer. As shown in Figure 1A, within the entire wavelength range tested, the exemplary articles of the present invention exhibited EMI attenuation that was on the order of 2 to 5 orders of magnitude greater than the EMI attenuation of the non-homogeneous control. Table 1 below shows exemplary compositions of articles of the invention, which exhibit high EMI shielding even at CNT concentrations as low as 0.005-1 wt %. [Table 3]
[0154] The pristine polymer, having substantially the same dimensions as the test sample, exhibited negligible attenuation (approximately 0-5 dB). Additionally, as shown in Figures 1B-1C, the exemplary articles processed from the core-shell particles of the present invention were characterized by a substantially homogenous distribution within the polymer matrix, as shown in Figure 1B, and exhibited a substantially uniform distribution of CNTs without any detectable aggregates. In contrast, P9-158-1 was characterized by a non-homogeneous distribution (and even phase separation) of CNTs, with visually detectable CNT aggregates on the article surface (see Figure 1C).
[0155] While the present invention has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations will be apparent to those skilled in the art. Accordingly, the present invention is intended to embrace all such alternatives, modifications and variations that fall within the spirit and broad scope of the appended claims. All publications, patents, and patent applications mentioned herein are incorporated herein by reference in their entirety to the same extent as if each individual publication, patent, and patent application was specifically and individually indicated to be incorporated by reference. Furthermore, citation or identification of any document in this application should not be construed as an admission that such document is available as prior art to the present invention. To the extent section headings are used, they should not be construed as necessarily limiting.
Claims
1. A particle comprising a polymer core in contact with a shell comprising CNTs, said polymer core comprising a thermoplastic polymer and having a size between 1 and 2000 μm.
2. 2. The particle of claim 1, wherein the weight percentage of the CNTs in the particle is 0.00001-5%.
3. 3. The particle of claim 1 or 2, wherein the polymer has a volume resistivity of at least 10 Ω cm and the CNTs are single-walled CNTs (SWCNTs).
4. The particle of claim 1 , wherein the shell comprises a surfactant.
5. The particle of claim 4 , wherein the surfactant is a cationic surfactant.
6. The particle of claim 5, wherein the cationic surfactant comprises a polyalkylammonium-co-polyether.
7. 5. The particle of claim 4, wherein the weight / weight ratio of the surfactant to the CNTs is from 10:1 to 0.5:
1.
8. The particle of claim 1 , wherein the thermoplastic polymer is characterized by a melting temperature of at least 100° C.
9. A composition comprising a plurality of particles according to claim 1.
10. 10. The composition of claim 9, further comprising an additive, wherein a weight / weight ratio between the additive and the plurality of particles in the composition is from 1:100 to 100:
1.
11. The composition of claim 10 , wherein the additive comprises glass fibers, polymer particles, or both.
12. The composition of claim 9, wherein the composition is characterized by a melt flow index (MFI) of 0.1 to 100.
13. 10. The composition of claim 9, which is extrudable and wherein the weight portion of (i) the CNTs, or (ii) the surfactant, within the composition is, independently, 0.01-5%.
14. 1. An article comprising a thermoplastic polymer, a surfactant, and a plurality of CNTs homogeneously distributed therein, wherein the weight percentage of (i) the CNTs, or (ii) the surfactant, within said article is, independently, 0.01-5%.
15. An article according to claim 14, produced by processing a composition according to any one of claims 9 to 13.
16. 16. The article of claim 14 or 15, characterized by a volume resistivity of 1012 to 1 Ω cm.
17. 15. The article of claim 14, wherein each of (i) the CNTs and (ii) the surfactant are independently present in the article at a weight / weight concentration of 0.01% to 5%; and characterized by a volume resistivity of 1010 to 102 Ω cm.
18. The article of any one of claims 14-17, wherein the CNTs are SWCNTs; the surfactant is a cationic surfactant, optionally comprising a polyalkylammonium-co-polyether; and the thermoplastic polymer is characterized by a melting temperature of at least 100°C.
19. The article of claim 14, wherein a weight / weight ratio of the surfactant to the CNTs is from 10:1 to 0.5:
1.
20. 16. The article of claim 15, wherein the processing is by any of extrusion, injection, hot blown film, and molding or any combination thereof.
21. a) providing the composition under conditions suitable for extrusion, thereby obtaining an extrudate; and b) shaping said extrudate to obtain said article of the invention, forming said extrudate, said composition comprising particles comprising a polymer core in contact with a shell comprising CNTs, said polymer core comprising a thermoplastic polymer and having a size between 1 and 2000 μm; 15. A method for making the article of claim 14, comprising:
22. 22. The method of claim 21, wherein said step a) further comprises drying said extrudate under suitable conditions.